ANALYSIS OF BARRIERS TO PROCUREMENT OF E-PURCHASING GOODS AND SERVICES IN THE PURCHASE OF DOMESTIC PRODUCTS: A CASE STUDY OF THE NORTH SUMATRA PROVINCIAL PROCUREMENT BUREAU: (ANALISIS HAMBATAN PENGADAAN BARANG DAN JASA E-PURCHASING DALAM PEMBELIAN PRODUK DALAM NEGERI: STUDI KASUS BIRO PENGADAAN BARANG DAN JASA PROVINSI SUMATERA UTARA) - Syafrial Aulia Hutasuhut; Erika Revida; Muhammad Arifin Nasution (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Efforts to increase the purchase of domestic products as a step of economic development, especially local industries, face serious challenges. Product quality has not been maximized, complicated regulations are part of the problem. This study aims to describe problems related to obstacles to the procurement of goods and services through the e-purchasing method at the North Sumatra Provincial Goods and Services Procurement Bureau. This study uses a qualitative descriptive method and uses a case study approach. The study was conducted at the Goods and Services Procurement Bureau of the Regional Secretariat of North Sumatra Province which is located in the center of Medan City. There are two types of data in this study, namely primary data including primary data, then secondary data, namely supporting data, both data come from the collection of research documents, interviews and observations during the research process. The analysis focuses on the factors that affect the effectiveness of procurement of goods and services through e-purchasing in the North Sumatra Province area. The results of the study illustrate that obstacles in the procurement of goods and services are caused by aspects of the quality of local products that still do not reach the desired standards, so that this has an impact on the limited supply of existing goods. Most local product providers have also not followed administrative regulations so that some goods that are considered to meet the desired quality are hampered, this situation is mostly felt by small and medium-sized providers of goods and services. As for the obstacles to e-purchasing as a method of providing goods and services that are perfect, including the lack of knowledge of goods and services providers related to the work system and its regulations. This is due to the lack of information, socialization, and education provided by the government in strategic areas of the center of goods and services providers. This research is expected to be able to be considered and input for making regulations for local industrial development in the North Sumatra Province area.